The Role of The School Environment in Shaping Students' Character Through School Culture - Dewi Inayatun; Ellen Prima (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Character formation has become an increasingly important concern in contemporary education due to rapid social and technological changes that influence students’ behavior and values. This study examines the role of the school environment in shaping students’ character through school culture using a qualitative literature review approach. Data were collected from peer-reviewed journal articles, research reports, and academic publications related to character education, school culture, and school environmental factors. The findings indicate that character development is influenced by the interaction of several school environmental components, including teacher role modeling, school culture and climate, habituation practices, extracurricular activities, and social interactions. These components function as an integrated educational ecosystem that supports the internalization of values such as discipline, responsibility, honesty, cooperation, and respect. The review further reveals that character education is most effective when institutional values are consistently reflected in daily school practices and reinforced through meaningful participation in school activities. Strengthening school culture is therefore essential for fostering sustainable character development and supporting students’ holistic growth.